Analisis Bioetanol dari Limbah Kulit Buah Sukun (Artocarpus altilis) dengan Cara Hidrolisis dan Fermentasi - Fardiana, Fardiana; Ningsih, Purnama; Mustapa, Kasmudin (Universitas Tadulako, 2018)
This study aimed to determine glucose and ethanol levels from fermentation of peel waste of breadfruit. Glucose level was determined using UV-Vis spectrophotometer and then continued with fermentation of glucose from hydrolysis process using yeast tape (saccharomyces cerevisiae) for 3 days to produce bioethanol. The step in this study was the sample preparation, the acid variations in hydrolysis with HCl, H2SO4, H3PO4 (10%) and the fermentation. Determination of ethanol from the fermentation of glucose was measured by using alkoholmeter. The highest glucose level was 0.68% which was from hydrolysis using HCl and the highest ethanol level was 9% which obtained from the fermentation of glucose by using HCl hydrolysis. The conclusion shows that the type of acid used to reach optimum hydrolysis of the breadfruit’s peel is HCl.